Simultaneous equation and area under the curve spectrophotometric methods for estimation of cefaclor in presence of its acid induced degradation product; A comparative study - Khalid A.M. Attia; Nasr M. Elabasawy; Ebrahim Abolmagd (SpringerOpen, 2017)
Two simple spectrophotometric methods were developed and validated for determination of cefaclor in presence of its acid induced degradation product; namely simultaneous equation method using two wavelengths 265 and 235 nm Method (A) and Area under the curve method using two wavelength ranges (230-240) nm and (260-270) nm Method (B). The accuracy, precision and linearity ranges of the proposed methods were determined. The methods were validated and the specificity was assessed by analyzing synthetic mixtures containing the drug and its degradate. The two methods were applied for the determination of the cited drug in its pharmaceutical preparation and the obtained results were statistically compared with those of a reported method. The comparison showed that there is no significant difference between the proposed methods and the reported method regarding both accuracy and precision.